Meningkatkan Hasil Belajar Matematika Pokok Bahasan Pengoperasian Bentuk Aljabar Melalui Model Pemberian Tugas - Joko Santoso; Fatimatul Khikmiyah; Syaiful Huda (Postulat : Jurnal Inovasi Pendidikan Matematika, 2021)
Implementation of this research was conducted in Oktober to Nopember 2020. The purpose of this study is to obtain information about student learning outcomes in the subject matter in the algebra class VIID SMPN 1 Margomulyo after using the method of giving gssignment model. The subject of this research is the students of class VIID SMPN 1 Margomulyo in odd semester of academic year 2020-2021 with the number of students 26 students consisting of 10 men and 16 women. This classroom action research is implemented in 3 cycles consisting of one meetings each. Data collection is done by using learning result test, observation, and student's response. Then the research analyzed qualitatively and quantitatively. From the analysis results of third cycles obtained learners' learning completeness on the subject of Operation Calculate Algebraic Form is increased. This can be seen from the improvement of students' learning mastery that is the result of post test prasiklus value that experienced 15.38% completeness, in cycle 1 to 23.08%, in cycle 2 increased to 33.33%, and in cycle 3 increased to 92.31%.. This it can be concluded that from the third complete test result of learning as much as 92.31% so it can be said that learners learn mastery can be achieved. From the observation of the three cycles also experienced increased learning activities of learners, learners are increasingly more enthusiastic to follow the learning, active cooperative, daring to ask